Do dirty and clean energy investments react to infectious disease-induced uncertainty? - Dutta, Anupam; Park, Donghyun; Uddin, Gazi Salah; Kanjilal, Kakali; Ghosh, Sajal (Elsevier, 2024)
Following the outbreak of novel coronavirus, numerous studies have assessed the effect on global financial markets. However, investigations into whether, and to what extent, dirty and clean energy asset classes are sensitive to contagious diseases are rare. This study aims to fill this gap in the literature. We measured the effects of contagious viruses using the recently introduced infectious disease-related uncertainty index (EMVID). Our data include the iShares Global Energy ETF and clean energy stock indices from leading economies such as the United States, the European Union, Japan, and China. Employing the GARCH-MIDAS model, we find that the uncertainty associated with infectious diseases has a significant positive (negative) effect on the realized volatility (RV) of dirty (green) assets. This finding is novel given that it indicates the potential for “green recovery” in the post-pandemic era. Our findings further document that EMVID has significant predictive content for the volatility of these assets and that inserting the EMVID index into the GARCH-MIDAS process produces better volatility predictions than other uncertainty measures, including the crude oil volatility (OVX), geopolitical risk (GPR), and economic policy uncertainty (EPU) indices. Hence, the EMVID provides additional information not contained in the OVX, GPR, or EPU during the pandemic period. Our findings will be useful for energy market participants to make appropriate asset allocation decisions during pandemics.
Keywords: Clean energy investments; Dirty assets; Infectious disease-induced uncertainty; Sustainability; Volatility forecast; COVID-19; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|